Associations between the helpfulness of teacher induction programs, teacher self-efficacy, and anticipated first-year teacher retention - Han, Xiaotian (Frontiers in Psychology, 2023)
First year teachers need help because they are besieged with various challenges and are more likely to leave the professions within short years. Evidence-based TIPs have shown great potential in improving overall teachers’ performance and students’ outcomes. However, this consequence was argued. The purpose of the study was to: (a) determine to what extent the formalized teacher induction programs (TIPs) in Shanghai are perceived to be helpful for first-year public primary school teachers; (b) measure teacher self-efficacy and anticipated job retention of first-year teachers in Shanghai public primary schools; and (c) examine the degree to which these perceptions of helpfulness, teacher self-efficacy, and anticipated job retention are associated. The study employed Horn et al.’s (2002) high-quality TIP model as the theoretical framework. An online survey was completed by 408 first-year primary school teachers. Results showed that: (1) Perceptions regarding TIP helpfulness, overall, were not found to significantly correlate with teacher self-efficacy. (2) To a limit extent (r= -.142, p<.01) self-efficacy scores negatively correlate with anticipated retention such that those expressing higher levels of teacher self-efficacy are those with lower anticipated teacher retention scores, whereas a positive association was hypothesized. ( 3) with gender, major, and TIP helpfulness ratings all accounting for statistically significant proportions of unique variation in anticipated retention. Additional findings, implementations, and suggestions are also discussed in the research.